2023
DOI: 10.1002/jnr.25221
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress following spinal cord injury: From molecular mechanisms to therapeutic targets

Mengsi Yu,
Zhiying Wang,
Dongmin Wang
et al.

Abstract: Spinal cord injury (SCI) is a medical condition that results from severe trauma to the central nervous system; it imposes great psychological and economic burdens on affected patients and their families. The dynamic balance between reactive oxygen species (ROS) and antioxidants is essential for maintaining normal cellular physiological functions. As important intracellular signaling molecules, ROS regulate numerous physiological activities, including vascular reactivity and neuronal function. However, excessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 163 publications
(214 reference statements)
0
9
0
Order By: Relevance
“…Ferrous ions can participate in the aforementioned lipid peroxidation through Fenton reaction, generating a large amount of ROS, thereby causing secondary lipid peroxidation and further exacerbating oxidative stress ( 33 ). ROS can also react with C-H, S-H, N-H, or O-H in proteins, mediating the cleavage of peptide chains and modification of amino acid side chains, leading to protein misfolding, altered protein function, and increased susceptibility to hydrolysis and degradation ( 34 ). Experimental study ( 35 ) have shown that after SCI, proteins in the spinal cord are easily oxidized by oxidants to form advanced oxidation protein products.…”
Section: The Relationship Between Sci With Oxidative Stressmentioning
confidence: 99%
“…Ferrous ions can participate in the aforementioned lipid peroxidation through Fenton reaction, generating a large amount of ROS, thereby causing secondary lipid peroxidation and further exacerbating oxidative stress ( 33 ). ROS can also react with C-H, S-H, N-H, or O-H in proteins, mediating the cleavage of peptide chains and modification of amino acid side chains, leading to protein misfolding, altered protein function, and increased susceptibility to hydrolysis and degradation ( 34 ). Experimental study ( 35 ) have shown that after SCI, proteins in the spinal cord are easily oxidized by oxidants to form advanced oxidation protein products.…”
Section: The Relationship Between Sci With Oxidative Stressmentioning
confidence: 99%
“…Emerging data have shown that the depletion of KDM6A promotes intrinsic neural regeneration, vascular regeneration, and neural repair, thus benefiting functional recovery post SCI [ [20] , [21] , [22] ]. The imbalance between ROS and antioxidants participates in the functional and pathological impairment after SCI [ 23 ]. NADPH oxidases are a vital source for ROS, and NOX4 is a member of the NADPH oxidase family and plays a driving role in apoptosis, ROS production, and inflammatory responses post SCI [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The free ion is then able to readily generate reactive oxygen species (ROS) by way of the Fenton reaction [32]. ROS and cytokine signaling drive the inflammatory process towards an apoptotic state [33].…”
mentioning
confidence: 99%